Mengurai Fenomena Echo Chamber : Implikasi untuk Partisipasi Politik di Kalangan Generasi Muda - Alifia Aqida; Salwa Aidah; Amalia, Aida Restu (Jurnal Inovasi Komunikasi, 2025)
The echo chamber phenomenon is increasingly relevant in the context of political communication, especially among the younger generation who actively use social media. This situation creates a homogeneous information environment, where existing views and beliefs are reinforced, potentially reducing diverse political participation. This study aims to analyze the concept of the echo chamber and its impact on political participation among the younger generation, as well as identify effective strategies to reduce these impacts and increase political engagement. The method used is a literature study, in which researchers collect and analyze literature related to this phenomenon. The results of the study indicate that the echo chamber can cause polarization and political apathy among the younger generation. Recommendations produced include the need for better media education, increasing political literacy, and promoting open dialogue between groups with different views. With these steps, it is hoped that the younger generation can be more actively and inclusively involved in the political process, creating a more democratic society.